Biomimetic Dp44mT-nanoparticles selectively induce apoptosis in Cu-loaded glioblastoma resulting in potent growth inhibition. (October 2022) - Ismail, Muhammad; Yang, Wen; Li, Yanfei; Wang, Yibin; He, Wenya; Wang, Jiefei; Muhammad, Pir; Chaston, Timothy B.; Rehman, Fawad Ur; Zheng, Meng; Lovejoy, David B.; Shi, Bingyang
Abstract: Selective targeting of elevated copper (Cu) in cancer cells by chelators to induce tumor-toxic reactive oxygen species (ROS) may be a promising approach in the treatment of glioblastoma multiforme (GBM). Previously, the Cu chelator di-2-pyridylketone-4, 4-dimethyl-3-thiosemicarbazone (Dp44mT) attracted much interest due to its potent anti-tumor activity mediated by the formation of a highly redox-active Cu-Dp44mT complex. However, its translational potential was limited by the development of toxicity in murine models of cancer reflecting poor selectivity. Here, we overcame the limitations of Dp44mT by incorporating it in new biomimetic nanoparticles (NPs) optimized for GBM therapy. Biomimetic design elements enhancing selectivity included angiopeptide-2 functionalized red blood cell membrane (Ang-M) camouflaging of the NPs carrier. Co-loading Dp44mT with regadenoson (Reg), that transiently opens the blood-brain-barrier (BBB), yielded biomimetic Ang-MNPs@(Dp44mT/Reg) NPs that actively targeted and traversed the BBB delivering Dp44mT specifically to GBM cells. To further improve selectivity, we innovatively pre-loaded GBM tumors with Cu. Oral dosing of U87MG-Luc tumor bearing mice with diacetyl-bis(4-methylthiosemicarbazonato)-copperII (Cu(II)-ATSM), significantly enhanced Cu-level in GBM tumor. Subsequent treatment of mice bearing Cu-enriched orthotopic U87MG-Luc GBM with Ang-MNPs@(Dp44mT/Reg) substantially prevented orthotopic GBM growth and led to maximal increases in median survival time. These results highlighted the importance of both angiopeptide-2 functionalization and tumor Cu-loading required for greater selective cytotoxicity. Targeting Ang-MNPs@(Dp44mT/Reg) NPs also down-regulated antiapoptotic Bcl-2, but up-regulated pro-apoptotic Bax and cleaved-caspase-3, demonstrating the involvement of the apoptotic pathway in GBM suppression. Notably, Ang-MNPs@(Dp44mT/Reg) showed negligible systemic drug toxicity in mice, further indicating therapeutic potential that could be adapted for other central nervous system disorders.